Metal ions synergize with gangue minerals to remove residual sodium oleate from mineral processing wastewater. (15th February 2023) - Meng, Xiangsong; Jiang, Min; Lin, Shangyong; Gao, Zhiyong; Han, Haisheng; Wang, Li; Zhang, Chenyang; Liu, Ruohua; Bao, Huanjun; Wu, Meirong; Jing, Gaogui; Sun, Wei
Abstract: The removal of residual organic flotation reagents from mineral processing wastewater (MPW) can be divided into two steps: the tailings pulp settles in the tailings reservoir, and the effluent from the reservoir is treated in a wastewater treatment station. To simplify the wastewater treatment process, this work explored the fundamental problems of removing residual sodium oleate (NaOl) from tailings wastewater by one step starting from tailings pulp treatment. The removal behavior and mechanism of NaOl from wastewater by metal ions combined with gangue minerals in the tailings pulp were studied. The concentration of NaOl was determined using chemical oxygen demand (COD). Results showed that the newly prepared 100 mg/L NaOl solution formed NaOl colloid after a period of time, and Fe 3+ and Al 3+ were more conducive to the COD removal of NaOl colloid than Ca 2+ . Moreover, metal ions and gangue minerals played a synergistic role in enhancing the COD removal of NaOl colloid. Mechanism analysis showed that the unit charge solubility of FeOl3 or AlOl3 was much lower than that of CaOl2, so Fe 3+ or Al 3+ was more likely to precipitate with NaOl than Ca 2+ . The addition of Fe 3+ or Al 3+ to NaOl colloid reduced the absolute value of the zeta potential of the suspended solids under suitable pH conditions, leading to colloid condensation. When metal ions and gangue minerals coexisted, gangue minerals adsorbed part of NaOl and played the role of coarse particles carrying fine particles to settle. This finding can be used to explain the synergistic effect of metal ions and gangue minerals. The study provides a new idea for the treatment of MPW and has great application prospect. Graphical abstract: Image 1 Highlights: Fe 3+ and Al 3+ were more conducive to the COD removal of NaOl colloid than Ca 2+ . The unit charge solubility product of Fe(Ol)3 and Al(Ol)3 was much lower than that of Ca(Ol)2 . Metal ions and gangue minerals played a synergistic role in enhancing COD removal. Gangue minerals can play the role of coarse particles carrying fine particles to settle.